The Hellenic landscape and the renewable energy sources: A social survey (2022) and some considerations - Kosmopoulos, Panos (Technical Annals, 2023)
The aim of this paper is to underline the urgent need for the application of R.E.S. in Greece, the related problems regarding the natural environment, the archaeological sites, the traditional architecture, and the existing contemporary urban environment. Some references to the theoretical approaches of the subject of environmental Aesthetics are also mentioned. The method to achieve conclusions has been a social survey of the opinions of Greek people, regarding their surrounding environment and the application of R.E.S.. Concluding the economic factor proves to be very important, primarily at the individual level and then at the social or national level, and the aesthetic factor seems to follow the economic one, but is also very important.